Biologics for the treatment of pyoderma gangrenosum in ulcerative colitis - Arivarasan, K (Intest Res, 2016)
Pyoderma gangrenosum (PG) is an uncommon extra-intestinal manifestation of inflammatory bowel disease (IBD). Despite limited published literature, biologics have caused a paradigm shift in the management of this difficult-to-treat skin condition. The clinical data and outcomes of three patients with active ulcerative colitis and concurrent PG treated with biologics (infliximab two and adalimumab one) are reviewed in this report. Biologics were added because of the sub-optimal response of the colonic symptoms and skin lesions to parenteral hydrocortisone therapy. All three patients showed a dramatic response to the addition of the biologics. In view of the rapid healing of the skin lesions, superior response rate, and the additional benefit of improvement in the underlying colonic disease following treatment, anti-tumor necrosis factor blockers should be considered as a first line therapy in the management of PG with underlying IBD.